2019
DOI: 10.1016/j.ymeth.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibodies: Potential immunotherapies for HIV treatment

Abstract: Bispecific (bs) antibodies (Abs, bsAbs) are engineered immunoglobulins that contain two different antigen-binding sites in one molecule. bsAbs can be divided in two molecular formats; the IgGlike and non-IgG like. The structural elements of each format have implications for engaging the immune system. Elimination of HIV will need sophisticated approaches with immunotherapies being one of the strategies under investigation. Furthermore, HIV genetic variability and functional compromise of the adaptive CTL respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 95 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…showed that this bispecific antibody bound to EBOV is internalized into endo-lysosomal compartments where it potently blocks Ebola interaction with its intracellular receptor 28 . This strategy, already tested for HIV 29 , has been shown to protect mice, even when administered 2 days after challenge with EBOV 28 .…”
Section: Inhibition Of Receptor Bindingmentioning
confidence: 99%
“…showed that this bispecific antibody bound to EBOV is internalized into endo-lysosomal compartments where it potently blocks Ebola interaction with its intracellular receptor 28 . This strategy, already tested for HIV 29 , has been shown to protect mice, even when administered 2 days after challenge with EBOV 28 .…”
Section: Inhibition Of Receptor Bindingmentioning
confidence: 99%
“…Antibody-based target cell killing has been advanced in cancer treatment and is moving to the forefront of therapeutic approaches against diverse viral pathogens, including HIV-1. Specific efforts include adoptive transfer of T cells, e.g., natural virus-specific T cells expanded ex vivo [ 35 ] or genetically modified T cells expressing cloned T-cell receptors or chimeric antigen receptors [ 36 , 37 ]; another T-cell-mediated technology involves bispecific T-cell-engaging antibodies [ 38 ]. Distinct from these technically complex cell-mediated strategies, RIT technology typically involves intravenous infusion of a purified protein for direct killing of infected cells [ 39 , 40 ]; RITs targeting HIV-1 and other specific viral pathogens have been described [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach for more individualized treatment in future applications is a logical choice for treatment such as targeting host proteins or engineered multi-targeting antibodies become more available. The requirement for cocktails of bNAbs has long been realized, but new ideas for combination therapy include using specifically engineered antibody molecules with the capability to target multiple epitopes (127)(128)(129)(130), such as bi-specific antibodies (bsAbs) (131)(132)(133), with the 10E8.4/iMab now in clinical trials. Bispecific T-cell engagers (BiTEs) have been developed so far primarily for oncology (134)(135)(136), but now also for HIV therapeutics (137).…”
Section: Isotype and Multi-epitope Targetingmentioning
confidence: 99%